Afro-Futurism or Lament? Staging Africa(s) in Dance Today and in the 1920s. Issue 1 (19th April 2017) - Haitzinger, Nicole
Abstract : This article analyzes two contemporary pieces, Faustin Linyekula's La Création du Monde 1923–2012 and Vera Mantero's A mysterious thing said e. e. Cummings, which respond to dance productions presented in Europe in the early decades of the twentieth century by criticizing their "negrophilic" attitude. The article juxtaposes the analysis of these two contemporary pieces with rereadings of the historical choreographies/events of the 1920s to which they refer, namely, Les Ballets Suédois's La Création du Monde (1923) and Josephine Baker's performances. Theoretically revisiting historical works that developed within such a "negrophilic" framework alongside contemporary pieces relating to them can be taken as attacking this very framework, trying to "undo" the Eurocentrism inherent in its cannibalistic processes. Such a perspective may allow for the acknowledgement of plural, multiple views of Africanistic presences in an otherwise "negrophilic" context.